SISTEM INFORMASI KUALITAS AIR SUNGAI DI WILAYAH SUNGAI SEPUTIH SEKAMPUNG - Dyah Indriana Kusumastuti; Endro Prasetyo Wahono; Anggraini, Witta Putri (BRILIANT: Jurnal Riset dan Konseptual, 2024)
The WebGis-based water quality information system is designed to facilitate more effective monitoring, management, and storage of water quality data for government agencies and the public. The main objective of this system is to build an information platform on water quality conditions across various regions, making it easier for government agencies to make decisions regarding water quality management and mitigating potential environmental risks. This study analyzed water quality using the Pollution Index (PI) method in the Seputih Sekampung River Basin from 2019 to 2023. The results of the water quality calculations showed that the decline in water quality was predominantly caused by human activities, particularly high levels of E. coli or Total Coliform. This decline was also consistent with changes in land cover in the area. The system development was carried out using the prototyping method and tested using User Acceptance Testing. The study results indicate that the developed system is capable of managing water resource data in Lampung Province and presenting this information to users through a WebGIS interface. Through data integration, it is expected that efforts to protect water quality resources will become more optimal and sustainable.